2021
DOI: 10.3390/biom11020330
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Molecular Modeling Evaluation of Food Peptides to Inhibit Key Targets of COVID-19 Virus

Abstract: Peptide drugs, especially food-derived peptides, have a variety of functional activities including antiviral and may also have a therapeutic effect on COVID-19. In this study, comparing with the reported drugs, 79 peptides were found to bind to the key targets of COVID-19 virus with higher non-covalent interaction, while among them, six peptides showed high non-covalent interactions with the three targets, which may inhibit the COVID-19 virus. In the simulation, peptides of nine to 10 amino acids with a hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Although some of the studies in this overview included molecular dynamics as a post-docking assessment, many lack additional data processing steps. The short production times of molecular dynamic simulations used in some studies also risk missing important changes in binding stability [ 43 , 47 , 58 ], changes of which occur over timescales of 100–200 ns [ 19 , 22 • ]. Specific workflows may also be required depending on the analytes evaluated.…”
Section: Critical Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the studies in this overview included molecular dynamics as a post-docking assessment, many lack additional data processing steps. The short production times of molecular dynamic simulations used in some studies also risk missing important changes in binding stability [ 43 , 47 , 58 ], changes of which occur over timescales of 100–200 ns [ 19 , 22 • ]. Specific workflows may also be required depending on the analytes evaluated.…”
Section: Critical Interpretation Of Resultsmentioning
confidence: 99%
“…Wahedi et al [ 46 ] evaluated stilbenes, which are associated with anti-tumor, anti-inflammatory, and other biological activities, with the aim of repurposing them as agents against COVID-19 and found that resveratrol may have potent activity inhibiting the host-virus interactions mediated by SARS-CoV-2 spike protein. Food-derived peptides with purported anti-hypertensive activity were predicted to interact with various targets of SARS-CoV-2 and demonstrated potential as lead compounds for COVID-19 treatment [ 47 ]. Nisin, a well-established and common food preservative with known antimicrobial activity, was reported for the first time to potentially possess antiviral activity via interactions with human angiotensin-converting enzyme 2, a protein involved in coronavirus-host recognition [ 48 ].…”
Section: Potential Sars-cov-2 Inhibitors From Foodsmentioning
confidence: 99%
“…The hydrophobicity of macrocyclic peptides is related to the anti-HIV activity; however, the mechanism of action is still unclear. 39,40 In a recent study, Shi et al (2021) successfully demonstrated that 79 peptides derived from natural food resources, including plant, animal, marine, and mushroom, can bind to key targets of the COVID-19 virus and may thus exert antiviral activity. 41 Among them, VSGAGRY from bitter melon seed, VMDKPQG from soybean, KDYRL from mung bean, NNNPFKF…”
Section: Antiviral Activitymentioning
confidence: 99%
“…In another appealing work, Shi and coworkers reported the identification of candidate foodderived peptides with ability to bind to three of the most important targetable SARS-CoV-2 proteins, namely angiotensin-converting enzyme type 2 (ACE2), key for viral entry, Mpro, and reversed transcriptase (RdRp) [24] . As for Mpro, the computational studies detected about 150 peptides able to occupy the protease binding site, and the interaction of the 30 highscored compounds were analyzed in detail.…”
Section: Peptides As Sars-cov-mpro Inhibitorsmentioning
confidence: 99%